A Swallowing Clinical Assessment Score (SCAS) to evaluate outpatients with Parkinson’s disease - Loureiro, Fernanda; Nóbrega, Ana Caline; Sampaio, Marília; Argolo, Natalie; Dalbem, André; Melo, Ailton; Gomes, Irenio (PAJAR - Pan-American Journal of Aging Research, 2013)
Aims: This study proposes a standardized Swallowing Clinical Assessment Score (SCAS) in PD. Methods: 174 idiopathic PD patients and 22 controls were evaluated in a transversal study. The SCAS comprised of twelve items that identify the occurrence of specific alterations in the oral and pharyngeal phases. Each alteration was given a weight in accordance to its relevance in compromising the act of swallowing. Results: The SCAS follows a theoretical scoring system ranging from 0 to 354 points, where zero corresponds to the ability to swallow without alteration. Scores ≤2 points indicate normal swallowing; functional swallowing ranges from ≥2 and ≤15 points; mildly altered ranges from ≥15 and ≤35 points; moderately altered ranges from ≥35 and ≤60 points. Scores in excess of 60 points indicate severe alteration. Conclusions: The SCAS proposed here is only part of the global assessment of dysphagia. Its main applications are: to screen swallowing difficulties in PD, even with no complaints, thus facilitating early diagnosis; to monitor the development of alterations in swallowing in an objective manner; and to assess the effectiveness of strategies for swallowing rehabilitation.